2015
DOI: 10.1590/s1679-87592015086206303
|View full text |Cite
|
Sign up to set email alerts
|

Population parameters and the relationships between environmental factors and abundance of the Acetes americanus shrimp (Dendrobranchiata: Sergestidae) near a coastal upwelling region of Brazil

Abstract: The population dynamics of Acetes americanus was investigated, focusing on the sex ratio, individual growth, longevity, recruitment and relationship between abundance and environmental factors in the region of Macaé, strongly influenced by coastal upwelling. Otter trawl net samplings were performed from July 2010 to June 2011 at two points (5 m and 15 m). Nearly 19,500 specimens, predominantly females (77.15%), were captured. Their sizes, larger than that of males, indicated sexual dimorphism. Shrimps at lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…distribution was primarily associated with higher temperatures and chlorophyll-a. Acetes americanus is known to have higher abundance in the months with high chlorophyll-a concentration (Santos et al, 2015) and it occurs in shallower sites with high temperatures and lower salinity values (Simões et al, 2013b); these patterns are similar to those found for Acetes spp. on ACS.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…distribution was primarily associated with higher temperatures and chlorophyll-a. Acetes americanus is known to have higher abundance in the months with high chlorophyll-a concentration (Santos et al, 2015) and it occurs in shallower sites with high temperatures and lower salinity values (Simões et al, 2013b); these patterns are similar to those found for Acetes spp. on ACS.…”
Section: Discussionsupporting
confidence: 71%
“…is well known; however, this was not evident on the ACS. Overall, recruitment is continuous throughout the year in tropical and subtropical regions, with spawning peaks occurring during hotter seasons (Xiao & Greenwood, 1993;Simões et al, 2013aSimões et al, , 2013bSantos et al, 2015). Acetes spp.…”
Section: Discussionmentioning
confidence: 99%
“…The sexual maturity index of A. indicus fluctuated annually, with the highest value occurring from June to August (Amin et al, 2009). A study of the population dynamics of Acetes americanus in the coastal upwelling area in Brazil found that the body lengths of females were significantly longer than those of males, and showed a substantial predominance (77%) in female abundance (Santos et al, 2015). Compared with high latitude regions, individuals (A. americanus) in low latitudes have significantly longer body lengths and lifespans (Santos et al, 2015).…”
Section: Reproduction and Population Dynamics Of Acetesmentioning
confidence: 99%
“…A study of the population dynamics of Acetes americanus in the coastal upwelling area in Brazil found that the body lengths of females were significantly longer than those of males, and showed a substantial predominance (77%) in female abundance (Santos et al, 2015). Compared with high latitude regions, individuals (A. americanus) in low latitudes have significantly longer body lengths and lifespans (Santos et al, 2015). In a study of the reproductive biology of A. chinensis on the western coast of the Korean Peninsula, mature female individuals appeared at the beginning of April and reached their maximum abundance in July, and there were no mature females after September (Oh & Jeong, 2003).…”
Section: Reproduction and Population Dynamics Of Acetesmentioning
confidence: 99%
“…Through this model it is possible to estimate the maximum size that the individuals can reach, and thus, their longevity. Bertalanffy's model is considered the best one to study age in crustaceans (Davanso et al, 2013;Santos et al, 2015;Pescinelli et al, 2018b).…”
Section: Growth Longevity and Mortality Of Alpheus Brasileiromentioning
confidence: 99%